2008
DOI: 10.1002/anie.200705931
|View full text |Cite
|
Sign up to set email alerts
|

A Transient VIII–Alkylidene Complex: Oxidation Chemistry Including the Activation of N2 to Afford a Highly Porous Honeycomb‐Like Framework

Abstract: Terminal vanadium alkylidenes [1][2][3][4] still constitute a rare class of complexes, and this type of functional group, when combined with this metal, has been far less explored than its heavier congeners niobium [5,6] and tantalum. [6] Part of this limitation revolves around the ability of vanadium to populate low-valent oxidation states, especially the + 3 state. As a result, alkylation reactions stemming from the high-valent metal complex often lead to reduction as opposed to the more prototypical transme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
39
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 26 publications
(42 reference statements)
8
39
0
Order By: Relevance
“…, with a short NN bond distance of 1.246(6)Å, as well as short imide VN bond (1.757(3)Å). 97 , 98 The lack of N 2 displacement by tBuCN is consistent with the proposal of V V centers. The same group later showed that N 2 can coordinate a V II complex featuring bulky NacNac and ArOligands, leading to two antiferromagnetically coupled V III centers bridged by the reduced end-on N 2 ligand (scheme 25).…”
Section: Scheme 24supporting
confidence: 86%
“…, with a short NN bond distance of 1.246(6)Å, as well as short imide VN bond (1.757(3)Å). 97 , 98 The lack of N 2 displacement by tBuCN is consistent with the proposal of V V centers. The same group later showed that N 2 can coordinate a V II complex featuring bulky NacNac and ArOligands, leading to two antiferromagnetically coupled V III centers bridged by the reduced end-on N 2 ligand (scheme 25).…”
Section: Scheme 24supporting
confidence: 86%
“…[66] Mindiola has reported the preparation of several vanadium(III), vanadium(IV), and vanadium(V) alkylidenes supported by β-diketiminate (nacnac) or PNP-pincer ligands, however no olefin metathesis activity was reported for these species. [67][68][69][70][71]…”
Section: Early Vanadium Alkylidenesmentioning
confidence: 99%
“…The following year, a vanadium(V) alkylidene was prepared through oxidation of a vanadium(III) precursor with a Wittig reagent ( II , Chart 1), however this complex demonstrated no reactivity towards NBE [66] . Mindiola has reported the preparation of several vanadium(III), vanadium(IV), and vanadium(V) alkylidenes supported by β‐diketiminate (nacnac) or PNP‐pincer ligands, however no olefin metathesis activity was reported for these species [67–71] …”
Section: Vanadiummentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] While N 2 elimination from diazoalkanes is generally facile upon reaction with metal complexes, the isolation and characterization of metal-bound diazoalkane adducts is possible and has yielded a plethora of complexes spanning multiple coordination modes. [6,7,13,14] Five coordination modes are possible for a diazoalkane moiety bound to a single transition metal center (Chart 1): κ 1 -N end-on coordination involving the terminal N (type A), [15][16][17][18][19][20][21][22] η 2 -N,N side-on (type B), [23][24][25][26][27][28] η 2 -C,N side-on (type C), κ 2 -C,N metallacyclic (type D), and κ 1 -C coordination (type E). Coordination of a diazoalkane to more than one metal atom is also possible.…”
Section: Introductionmentioning
confidence: 99%